2017
DOI: 10.1001/jamasurg.2017.0977
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Patient Decisions About Breast Reconstruction After Mastectomy

Abstract: IMPORTANCE Breast reconstruction has the potential to improve a person’s body image and quality of life but has important risks. Variations in who undergoes breast reconstruction have led to questions about the quality of patient decisions. OBJECTIVE To assess the quality of patient decisions about breast reconstruction. DESIGN, SETTING, AND PARTICIPANTS A prospective, cross-sectional survey study was conducted from June 27, 2012, to February 28, 2014, at a single, academic, multidisciplinary oncology clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 39 publications
4
61
1
Order By: Relevance
“…Furthermore, significantly more women who opted for breast reconstruction rated body image and sexuality important than those women who did not seek reconstruction [15]. Lee et al found that women preferring reconstruction found breast shape with or without clothes more important than women who did not seek reconstruction [21]. Nonetheless, our study did not show a significant difference in sexual well-being between the two groups at baseline, although the non-reconstruction group scored slightly higher.…”
Section: Discussioncontrasting
confidence: 75%
“…Furthermore, significantly more women who opted for breast reconstruction rated body image and sexuality important than those women who did not seek reconstruction [15]. Lee et al found that women preferring reconstruction found breast shape with or without clothes more important than women who did not seek reconstruction [21]. Nonetheless, our study did not show a significant difference in sexual well-being between the two groups at baseline, although the non-reconstruction group scored slightly higher.…”
Section: Discussioncontrasting
confidence: 75%
“…Overall, women’s knowledge, preparedness, and decision quality related breast reconstruction is relatively low (Lee, Deal, Huh, & et al, 2017; Manne et al, 2016; Pusic et al, 2012; Pusic et al, 2017). For example, although women may view their ability to return to normal activities or avoid complications from surgery as important in their decisions, their actual knowledge of these factors as they relate to reconstruction method appears limited (Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, although women may view their ability to return to normal activities or avoid complications from surgery as important in their decisions, their actual knowledge of these factors as they relate to reconstruction method appears limited (Lee et al, 2011). Of concern, a recent prospective study of over 100 women found that a majority underwent reconstruction despite endorsing preferences (e.g., desire to avoid complications) that were better aligned with mastectomy alone (Lee et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the beneficial effects of breast reconstruction on postoperative patient‐reported health‐related outcome measures . Clinical research has identified the importance of patient buy‐in, that is, shared decision‐making, when choosing the reconstructive modality . However, it is peculiar that after decades of breast reconstruction, patients continue to be generally offered only two options, that is, implant‐based reconstruction vs autologous reconstruction.…”
Section: Introductionmentioning
confidence: 99%